2018
DOI: 10.12944/crnfsj.6.3.22
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Nutritional and Sensory Properties of Cookies Formulated with Quinoa, Sweet Potato and Wheat Flour Blends

Abstract: The study was conducted to formulate cookies with and without partial replacement of wheat flour (W) with sweet potato (SP) and quinoa flour (Q) blends. Sweet potato flour and quinoa flour were blended in equal proportion and then incorporated at the levels of 20, 40 and 60% by replacing wheat flour to prepare cookies. The cookies formulations were: CI(Control, 100W), CII (80W+10Q+10SP), CIII (60W+20Q+20SP) and CIV (40W+30Q+30SP).The three flour types and the prepared cookies were accessed for their nutritiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
(16 reference statements)
0
6
0
3
Order By: Relevance
“…La harina de trigo es el componente principal para la elaboración de galletas, producto de la industria alimentaria; sin embargo, diversas investigaciones actualmente han valorado el uso de otras harinas a partir de otros cereales, tales como arroz, maní, quinua (Chopra et al, 2018); así como, legumbres (germen de algarrobo, harina de soya, garbanzo, lenteja, guisante), semillas (chia), frutas (grosella negra, fresa, granadilla etc) (Zegarra et al, 2019), para la obtención de este producto.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…La harina de trigo es el componente principal para la elaboración de galletas, producto de la industria alimentaria; sin embargo, diversas investigaciones actualmente han valorado el uso de otras harinas a partir de otros cereales, tales como arroz, maní, quinua (Chopra et al, 2018); así como, legumbres (germen de algarrobo, harina de soya, garbanzo, lenteja, guisante), semillas (chia), frutas (grosella negra, fresa, granadilla etc) (Zegarra et al, 2019), para la obtención de este producto.…”
Section: Introductionunclassified
“…Debido al contenido de aminoácidos esenciales de su proteína, la quinua es considerada como el único alimento del reino vegetal que provee todos estos aminoácidos, que se encuentran dentro de los estándares de nutrición humana establecidos por la FAO (Villanueva Chunque., 2019). Además, su perfil proteico similar al de la leche es fuente muy rica de calcio, magnesio, hierro y zinc y a diferencia del trigo, cebada, no contiene gluten, por lo tanto, puede servir como una alternativa importante para personas con enfermedad celíaca (Chopra et al, 2018).…”
Section: Introductionunclassified
“…Recently, the demand for consuming nutritionally rich products has been increasing among consumers, and these products are ready to eat, have a long shelf life, and are categorized as high and good quality protein contents [1]. Cookies are one of the interesting food products that add a new functional ingredient, because they are easy to prepare, have a long shelf life, and have good acceptance by the population [2], and they are considered as the largest category of snacks around the world [3].…”
Section: Introductionmentioning
confidence: 99%
“…Sesame seed is a staple food among many ethnic groups in Nigeria and it is cultivated in most areas of the middle belt, some Northern States of Nigeria (Olanyanju et al, 2006) and the temperate zones of the world. Myanmar is a major producer of sesame followed by India, China, Ethiopia and Nigeria (Nidhi et al, 2018). Sesame is an important source of oil (44 to 52.5%), protein (18 to 23.5%), carbohydrate (13%) (Kahyaoglu and Kaya, 2006;Bamigboye et al, 2010) and crude fibre (Obiajunwa et al, 2005), Johnson et al (1979) revealed that sesame seed contains 50% oil which is highly resistant to oxidation and 25% protein which has unique balance of essential amino acids and minerals.…”
Section: Introductionmentioning
confidence: 99%